2006
DOI: 10.1196/annals.1374.110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Commercially Available Assays for the Detection of IgM Phase II Antibodies to Coxiella burnetii in the Diagnosis of Acute Q Fever

Abstract: Four commercially available serological assays for the detection of IgM phase II antibodies in patients with acute Q fever infection were compared using a panel of 23 serum samples from patients with acute Q fever and 88 control sera from blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…The present study clearly shows that ELISAs have an important role in Q fever diagnostics, but they are not only limited in the distinction between acute, chronic, and past disease but also show large differences in sensitivity and specificity. Both our study and other studies demonstrate that the IFAT remains the most reliable test system for the serological diagnosis of Q fever (9,(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The present study clearly shows that ELISAs have an important role in Q fever diagnostics, but they are not only limited in the distinction between acute, chronic, and past disease but also show large differences in sensitivity and specificity. Both our study and other studies demonstrate that the IFAT remains the most reliable test system for the serological diagnosis of Q fever (9,(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 76%
“…For both systems, different commercial kits are available; these need to be tested and compared occasionally. In the 1990s and 2000s, several laboratories tested diverse ELISAs and IFATs mainly focused on the detection of phase II IgM antibody titers (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…A population-based survey or follow up of patients to obtain a convalescent sera sample was not feasible due to the nomadic lifestyle of the patients, the ongoing inter-clans conflicts and militia activities in the region. However previous studies have reported adequate performance of the used commercial serion ELISA classic test kits in detection of phase II specific IgG and IgM [ 36 , 62 ] respectively, in diagnosis of acute Q fever. The novelty of the present study was that the ELISA positive sera were further confirmed with the reference diagnostic method (IFA) and the patients whose fever onset was ≤ 2 weeks were further screened for Q fever using a quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, the ELISA also has a high sensitivity and good specificity. For example, in the diagnosis of acute Q‐fever in man, the ELISA has a reported sensitivity of 80% for anti‐phase II IgG and 84% for anti‐phase II IgM and a specificity of >99% in one study (Waag et al., ), and in a other study a specificity of 97.7% and sensitivity of 95.65% for anti‐phase II IgM (Frangoulidis et al., ).…”
Section: Discussionmentioning
confidence: 99%